(untitled) (MATEMATIKA, 2025)
The term "dual nature of ionising radiation" effectively captures the complex impacts of irradiation on human cells. This paper sheds light on the critical effects of irradiation on DNA structural integrity by examining double-strand breaks (DSBs). Our primary goal was to advance the existing model of bystander effects to facilitate the concurrent repair of multiple DNA DSBs, significantly enhancing the understanding of cellular response. We adopted the exponential matrix technique to solve a system of ordinary differential equations (ODEs) using MATLAB R2024a. Our refined model offers a comprehensive overview of cell populations and their DNA, explicitly addressing the number of DSBs and the incidence of mis-repaired breaks. Notably, this model considers the simultaneous repair of multiple DSBs, a crucial addition that allows for a more realistic representation of cellular dynamics. The simulation results reveal a remarkable 37% improvement in cell survival fractions compared to the existing model, underscoring a notable increase in DSB repair efficiency and overall cell viability. This indicates that our modified model outperforms the existing framework by facilitating greater DSB repair, ultimately leading to a higher survival fraction among cells exposed to radiation. These compelling findings demonstrate that our modified model provides a more accurate estimation of cellular response to irradiation than prior models. Furthermore, exploring alternative methods for solving the ODEs and integrating the cell cycle parameters into our framework could yield even more promising results. These insights are crucial for enhancing our understanding of DNA’s response to irradiation, paving the way for future innovations in cellular repair mechanisms.